Using coupons to encourage healthier child snack purchases in corner stores: results from the CHOMPS study - Mayer, Megan E.; McAlister, Anna R.; Economos, Christina D.; Mack, Suzanne; Plank, Kaela; Cash, Sean B. (Frontiers in Nutrition, 2024)
Objectives: To examine youths' (ages 6 -15 years) autonomous snack purchases in corner stores and pilot use of coupons to encourage more healthful snack purchases.Methods: This pilot study involved four corner stores proximal to K-8 schools in Massachusetts.Kids-only coupons of varying discounts were provided in store and paired with simple visual and verbal economic and health messages. Observational data about youths' autonomous snack purchases was recorded pre-and post-intervention. Outcomes of interest were snack item, price, and nutrient content. Comparisons of purchase characteristics and nutritional content across intervention conditions were made using Chi-squared and t-tests.Results: Across all stores, 2,973 purchase observations were recorded totaling approximately $6,000. Researchers estimated that about 55% of shoppers were 10-12 years old. Modest coupon usage (2.2% of purchases) was noted. However, candy purchases decreased, and the percentage of purchase events that included at least one healthier food item more than doubled, regardless of coupon use. Improvements in nutritional content of snacks were also observed.